2017
DOI: 10.1038/srep45860
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Hypoglossal to Tongue Musculature Motor Pathway by Remote Control

Abstract: Reduced tongue muscle tone precipitates obstructive sleep apnea (OSA), and activation of the tongue musculature can lessen OSA. The hypoglossal motor nucleus (HMN) innervates the tongue muscles but there is no pharmacological agent currently able to selectively manipulate a channel (e.g., Kir2.4) that is highly restricted in its expression to cranial motor pools such as the HMN. To model the effect of manipulating such a restricted target, we introduced a “designer” receptor into the HMN and selectively modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 43 publications
1
42
0
1
Order By: Relevance
“…Two previous studies used cre-dependent viral vectors to transduce hypoglossal motoneurons of ChAT-Cre+ mice with hM3Dq receptors 21,22 . Those studies identified that systemic administration of clozapine-N-oxide led to increased tongue muscle activity that enlarged the pharyngeal airspace in anesthetized mice 21 , and caused sustained tongue muscle activation across sleep-wake states in behaving mice 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies used cre-dependent viral vectors to transduce hypoglossal motoneurons of ChAT-Cre+ mice with hM3Dq receptors 21,22 . Those studies identified that systemic administration of clozapine-N-oxide led to increased tongue muscle activity that enlarged the pharyngeal airspace in anesthetized mice 21 , and caused sustained tongue muscle activation across sleep-wake states in behaving mice 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the identified properties are relevant to understanding and manipulating tongue motor control, in particular hypoglossal motor excitability and responsivity, that are key pathophysiological and phenotypic traits related to human OSA 5-8 . Such key properties of hypoglossal motor excitability and responsivity are not are amenable to systematic quantification using previous 'chemogenetic' approaches 21,22 given the inability to impose acute, precise and direct control over hypoglossal motor output using an intervention that can be transiently turned on and off, and graded in intensity, as is possible with photostimulation.The rationale for Study 1 in anesthetized mice was to interrogate the properties of hypoglossal motor output from the evoked motor responses using different protocols under stable conditions throughout the experiment (i.e., in the absence of spontaneous behaviors). The results from that study then led to the selection of one protocol to address properties of hypoglossal motor excitability and responsivity across naturally occurring sleep-wake states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of certain potassium channels at the hypoglossal motor pool can activate the tongue musculature throughout sleep to waking levels 40, 42 . Importantly, it has been recently shown that introducing a “designer” receptor into the hypoglossal motor pool, and selectively modulating it with a “designer” drug, led to significant and sustained increases in tongue muscle activity and increases in upper airway size in pre-clinical rodent models 60, 61 . Moreover, the increases in tongue muscle activity during sleep persisted for 8–10 hours, were of physiological pattern and magnitude, and were specific and selective for the tongue with no effects on diaphragm or postural muscle activities, or sleep-wake states 60 .…”
Section: Mapping Potential Drug Targets In the Circuitry Controllimentioning
confidence: 99%
“…Importantly, it has been recently shown that introducing a “designer” receptor into the hypoglossal motor pool, and selectively modulating it with a “designer” drug, led to significant and sustained increases in tongue muscle activity and increases in upper airway size in pre-clinical rodent models 60, 61 . Moreover, the increases in tongue muscle activity during sleep persisted for 8–10 hours, were of physiological pattern and magnitude, and were specific and selective for the tongue with no effects on diaphragm or postural muscle activities, or sleep-wake states 60 . These results support targeting a selective and restricted “druggable” target at the hypoglossal motor pool to activate tongue motor activity during sleep.…”
Section: Mapping Potential Drug Targets In the Circuitry Controllimentioning
confidence: 99%